Up close & personal Humanizing technology with Pahang Natives - Mohd Ferdaus, Musa (2019)
Some 35 undergraduates and scholarship recipients from University Malaysia Pahang (UMP) participated in an eye-opening programme of a Village Tour to the natives at Pos Menson in Cameron Highlands, Pahang, on March 23, 2019.